Relationship Between Marital Status and Condom Use Compliance among PSK in Puger Kulon - Dini Eka Pripuspitasari (Fetus : Journal of Midwifery, 2023)
Introduction: Condom use is highly recommended for commercial sex workers to prevent contracting sexually transmitted infections. However, condom use is often neglected, so condom use is often inconsistent. Based on data obtained at the Puger Health Center, commercial sex workers in Puger Kulon were 69 people (76.7%) of the data, commercial sex workers who experienced STIs were 47 people (68.1%). Objective: To determine the relationship between marital status and compliance with condom use among prostitutes in Puger Kulon. Methods: This research design uses a cross sectional method with a sample size of 30 respondents obtained using purposive sampling technique, data analysis using chi-square test. Results: The results of marital status on respondents were mostly in the category of alone (widow) 18 respondents (60%), while the results of condom use compliance on respondents were mostly in the non-compliant category 17 respondents (56.7%). Analysis: The result of chi square test is p = 0.004 <0.05. Ha is accepted or there is a relationship between marital status and compliance with condom use among prostitutes in Puger Kulon. Discussion: Married respondents tend to consistently use condoms. This is because married couples will pay more attention to safety in intercourse because they realize that having intercourse without using a condom will worsen their partner's health condition. It is hoped that this research can prevent and reduce the risk of STIs.